GERAKAN TAREQAT AKMALIYAH DI BANYUMAS JAWA TENGAH ABAD XIX - Sukardi, Tanto (Prodi. Pendidikan Sejarah FPIPS UPI dan APPS (Asosiasi peneliti dan Pendidik Sejarah), 2008)
The aim of the research is to study the form of Tareqat Akmaliyah movement in Banyumas Residency, Central Java, as the effect of the cultivation system applied in this area. The method used in this study is qualitative one, especially which is usually practiced in historical research, such as heuristics, critics, interpretation and explanation. In practice the cultivation system took a long time to grow and cultivate the plantation; hence the workers had little or no time at all to work at their own soil. Consequently, their families suffered a lot as their sawah or fields laid bare without producing food for their daily needs. In the long run, as these conditions getting worst, the families endured malnutrition, hunger, and high rate of mortality. Poverty forced these peasants and their families to make up and adjust new actions, attitudes, habits, and traditions as forms of self-defence mechanism to survive from the threat of oppression and exploitation. As one form their resistance against the cultivation system was social upheaval in the form of social moverment such as messianic movement.